2004
DOI: 10.1002/bit.20297
|View full text |Cite
|
Sign up to set email alerts
|

Physical and hydrodynamic properties of flocs produced during biological hydrogen production

Abstract: Dense flocs readily form in continuous culture bioreactors used for hydrogen production, but the fractal and hydrodynamic properties of these flocs have not been previously analyzed. We therefore examined the size distribution, fractal dimension, and hydrodynamic properties of flocs formed in a continuous flow, well-mixed reactor treating synthetic wastewater at a fixed condition of a 4.5 h hydraulic detention time (23jC, pH 5.5). The reactor was operated for a total of 3 months at three different organic load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 40 publications
3
22
0
5
Order By: Relevance
“…Many bacteria and mixed cultures are known to form biofilms, granules or flocs that were characterized by microscopy, physicochemical or biomolecular techniques [21][22][23][24][25]. Most of them highlighted that Clostridia were the dominant strains in the mixed microbial populations.…”
Section: /35mentioning
confidence: 99%
See 1 more Smart Citation
“…Many bacteria and mixed cultures are known to form biofilms, granules or flocs that were characterized by microscopy, physicochemical or biomolecular techniques [21][22][23][24][25]. Most of them highlighted that Clostridia were the dominant strains in the mixed microbial populations.…”
Section: /35mentioning
confidence: 99%
“…Indeed experiments not reported here showed floc formation of pure C. butyricum CWBI1009 cultures after a few sequences of SBR in 250 mL serum bottles without mixing. Zhang et al [24] and many authors already mentioned floc formation containing Clostridium hydrogen-producing strains. The experiments reported here confirm these observations for the pure C. butyricum CWBI1009 strain and that the sieve used at each sequence for the removal of spent culture medium was suitable to keep large flocs inside the bioreactor.…”
Section: /35mentioning
confidence: 99%
“…ethanol, butyrate) [2.3].It is found in previous studies [4,5,6] that the effluents of the hydrogen bioproduction process including mainly volatile fatty acids (VFAs) and alcohols can be reutilized to recover the thermal enthalpies and further produce methane. In this study, the anaerobic fermentation process was established using CSTR to investigate the potentiality of hydrogen bioproduction for various substrate COD concentrations and HRTs from sugary wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that aerobic granules are fractal-like aggregates composed by small particles. [7][8][9][10] For fractal aggregates, fractal dimension has been widely used to describe their irregular and complex structure, and it is useful in explaining some phenomena of aerobic granules.…”
Section: Introductionmentioning
confidence: 99%